Electrospun Nanocomposite Materials, A Novel Synergy of Polyurethane and Bovine Derived Hydroxyapatite - OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; BOZKURT, YAHYA (IOP PUBLISHING LTD, 2017)
Polyurethane (PU) is a synthetic polymer that is used for construction of scaffold in tissue engineering applications in order to obtain desirable mechanical, physical and chemical properties like elasticity and durability. Bovine derived hydroxyapatite (BHAp) is a ceramic based natural polymer that is used as the most preferred implant material in orthopedics and dentistry due to their chemically and biologically similarity to the mineral phase found in the human bone structure. PU and bovine derived hydroxyapatite (BHAp) solutions with different concentrations were prepared with dissolving polyurethane and BHAp in Dimethylformamide (DMF) and Tetrahydrofuran (THF) solutions. Blended PU-BHAp solutions in different concentrations were used for electrospinning technique to create nanofiber scaffolds and new biocomposite material together. SEM, FTIR and physical analysis such as viscosity, electrical conductivity, density measurement and tensile strength measurement tests were carried out after production process.
Keywords: SCAFFOLDS